Characterization of Lgr5‐positive epithelial cells in the murine thymus. Issue 5 (21st March 2013) - Vroegindeweij, Eric; van Mourik, Irene; Cupedo, Tom; Cornelissen, Jan J.
<x xml:space="preserve">Abstract</x> Leucine‐rich repeat‐containing G protein‐coupled receptor (Lgr)5 is a marker for epithelial stem cells in the adult intestine of mice. Lgr5 transcripts have also been detected in the developing murine thymus, leading to speculation that Lgr5 is a marker for the long‐sought stem cell of the thymus. To address the nature of the Lgr5‐expressing thymic epithelial cells (TECs), we used Lgr5‐GFP reporter mice. We show that epithelial cells expressing Lgr5 protein are present in the fetal thymus during a specific developmental window yet are no longer detectable at birth. To analyze the function of the Lgr5 protein during thymus development, we generated Lgr5−/− mice. These experiments unequivocally show that thymus development is not perturbed in the absence of Lgr5, that all TEC subsets develop in Lgr5−/− mice and that T cells are produced in the expected ratios. Finally, by using an inducible lineage tracing system to track the progeny of Lgr5+ fetal TECs in vivo, we demonstrated that Lgr5+ fetal TECs have no detectable progeny in the later fetal thymus. In sum, we show that presence of the Lgr5 protein is not a prerequisite for proper thymus organogenesis.